2016
DOI: 10.1007/s40279-016-0592-z
|View full text |Cite
|
Sign up to set email alerts
|

Practical Cooling Strategies During Continuous Exercise in Hot Environments: A Systematic Review and Meta-Analysis

Abstract: BackgroundPerforming exercise in thermally stressful environments impairs exercise capacity and performance. Cooling during exercise has the potential to attenuate detrimental increases in body temperature and improve exercise capacity and performance.ObjectiveThe objective of this review was to assess the effectiveness of practical cooling strategies applied during continuous exercise in hot environments on body temperature, heart rate, whole body sweat production, rating of perceived exertion (RPE), thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 58 publications
8
63
3
1
Order By: Relevance
“…Other studies confirmed this finding by using various cooling interventions during exercise, such as fanning [128,211], the application of an ice vest [123,212] and the ingestion of cold fluid [195,213]. Conversely, Ruddock's meta-analysis [129] showed no beneficial effects on heart rate, confirming improved endurance performance. Although the greatest improvement in performance was observed when both the core temperature and the heart rate were reduced by cooling [123], a possible improvement was also observed in the absence of a reduction in heart rate or core temperature [116][117][118]132].…”
Section: Cardiovascular Mechanismsmentioning
confidence: 89%
See 3 more Smart Citations
“…Other studies confirmed this finding by using various cooling interventions during exercise, such as fanning [128,211], the application of an ice vest [123,212] and the ingestion of cold fluid [195,213]. Conversely, Ruddock's meta-analysis [129] showed no beneficial effects on heart rate, confirming improved endurance performance. Although the greatest improvement in performance was observed when both the core temperature and the heart rate were reduced by cooling [123], a possible improvement was also observed in the absence of a reduction in heart rate or core temperature [116][117][118]132].…”
Section: Cardiovascular Mechanismsmentioning
confidence: 89%
“…Several reviews and meta-analyses have recently been published on the benefits of per-cooling [27,107,129]. However, no clear conclusion has been drawn regarding the effects of per-cooling on different types (i.e., 'aerobic', 'anaerobic' and cognitive) of performance.…”
Section: Effects Of Cooling During Exercise (Per-cooling)mentioning
confidence: 99%
See 2 more Smart Citations
“…Cooling is used as an acute strategy that has less physical and logistical demands than heat acclimation. It can be applied before exercise, at intervals or continuously during exercise and generally has favourable effects on exercise capability in hot environments [6][7][8][9]. Cooling strategies used during exercise, when the effects of heat strain are most pronounced, can be effective but there are few strategies that might be practically useful during continuous exercise in the heat.…”
Section: General Introductionmentioning
confidence: 99%